Límites de la narratividad: las artes de bien morir - Luis Galván (Les Cahiers de Framespa)
The artes moriendi tradition (15th-17th centuries) prototypically consists of a minimum of narrativity, the discourse form called «action description»; later texts show increasing narrativity, by means of concrete experiential data, or by particularly instantiating the enunciation. Moreover, there are «internal» limits of narrativity, those between descriptive or argumentative sections, and inserted exemplary stories. A significant increase of such stories pushes some late artes moriendi towards the borders between this edifying tradition and the entertaining genres.